Theoretical Study on Effect of Defective Connection to Reservoirs in an Atomic-Scale Conductor - Masato Morifuji (Advances in Condensed Matter Physics)
We theoretically investigate the effect of a defect at the interface between a conductor and reservoirs in an atomic-scale device. Since fabrication of atomic-scale contacts is a complex task, there could be defects at the interface between the conductor and reservoirs. Such defective contacts will make it difficult to measure currents properly. In this paper, we calculate current-voltage characteristics in two-dimensional devices with a defective connection to reservoirs by using the nonequilibrium Green’s function method. Results show that the magnitude of resistance change depends on the amplitude of quantized wave functions at the position of the defect.